2020
DOI: 10.21037/jtd-19-3802
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes of lobectomy vs. segmentectomy in non-small cell lung cancer with clinical T1N0M0 stage: a literature review and meta-analysis

Abstract: Background: Lobectomy has long been regarded as the standard treatment for operable non-small cell lung cancer (NSCLC). Recent studies suggested that segmentectomy could achieve a good prognosis for early-stage NSCLC and might be an alternative to lobectomy in this cohort. Until now, on the issue of comparison between lobectomy and segmentectomy, there remains no published randomized controlled trial (RCT), and all existing evidence is low. Recently, a categorization of lower-level evidence has been proposed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
(58 reference statements)
1
13
0
Order By: Relevance
“…Similarly, the MACH-NC meta-analysis, which investigated the effect of chemotherapy in addition to RT for 16485 patients across 87 randomized trials, reported an effect of chemotherapy on survival (HR 0.88), close to our BRACE-adjusted estimate. 32 While evidence regarding the comparative effectiveness of treatments for early stage NSCLC are conflicting, [33][34][35][36][37][38][39][40][41] our results indicated a survival advantage to lobectomy after BRACE correction. Though large randomized trials are lacking, in the meta-analysis by Zheng et al, the effect was attenuated in trials with higher levels of evidence.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Similarly, the MACH-NC meta-analysis, which investigated the effect of chemotherapy in addition to RT for 16485 patients across 87 randomized trials, reported an effect of chemotherapy on survival (HR 0.88), close to our BRACE-adjusted estimate. 32 While evidence regarding the comparative effectiveness of treatments for early stage NSCLC are conflicting, [33][34][35][36][37][38][39][40][41] our results indicated a survival advantage to lobectomy after BRACE correction. Though large randomized trials are lacking, in the meta-analysis by Zheng et al, the effect was attenuated in trials with higher levels of evidence.…”
Section: Discussionmentioning
confidence: 61%
“…Though large randomized trials are lacking, in the meta-analysis by Zheng et al, the effect was attenuated in trials with higher levels of evidence. 33 Of note, in some studies, lobectomy has been associated with higher 90-day mortality compared to stereotactic ablative radiotherapy (SABR); 41 if true, BRACE would under-correct for treatment selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is conflicting data in the literature regarding early‐stage NSCLC. A recent systematic review with meta‐analysis 15 included 12 nonrandomized studies involving 8072 participants and compared oncological outcomes of lobectomy versus segmentectomy in NSCLC patients with clinical T1N0M0. It showed that segmentectomy was associated with shorter overall survival (OS), but identified comparable disease‐free survival (DFS) for these patients and patients with nodules ≤2 cm 15 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review with meta‐analysis 15 included 12 nonrandomized studies involving 8072 participants and compared oncological outcomes of lobectomy versus segmentectomy in NSCLC patients with clinical T1N0M0. It showed that segmentectomy was associated with shorter overall survival (OS), but identified comparable disease‐free survival (DFS) for these patients and patients with nodules ≤2 cm 15 . However, when multivariate HRs were included, the impact of segmentectomy on OS and DFS was comparable to that of lobectomy in the entire cohort as well as in patients with nodules ≤2 cm.…”
Section: Discussionmentioning
confidence: 99%